2011
DOI: 10.1007/978-3-642-23771-3_43
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Modality in Notification Performance

Abstract: Abstract. The primary users of home care technology often have significant sensory impairments. Multimodal interaction can make home care technology more accessible and appropriate, yet most research in the field of multimodal notifications is not aimed at the home but at office or high-pressure environments. This paper presents an experiment that compared the disruptiveness and effectiveness of visual, auditory, tactile and olfactory notifications. The results showed that disruption in the primary task was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(75 citation statements)
references
References 22 publications
(45 reference statements)
3
71
1
Order By: Relevance
“…Providing multiple ways to interact can improve accessibility, which has prompted a number of researchers to call for the inclusion of multiple modalities in home care technology [11,19,25]. In addition, researchers have argued that dynamically switching between modalities when appropriate will also lead to increased user acceptability [1,18,30,31]; for example, switching to a more private modality (e.g. tactile) when delivering sensitive information in a social context might be desirable.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Providing multiple ways to interact can improve accessibility, which has prompted a number of researchers to call for the inclusion of multiple modalities in home care technology [11,19,25]. In addition, researchers have argued that dynamically switching between modalities when appropriate will also lead to increased user acceptability [1,18,30,31]; for example, switching to a more private modality (e.g. tactile) when delivering sensitive information in a social context might be desirable.…”
Section: Related Workmentioning
confidence: 99%
“…Warnock, McGee-Lennon & Brewster [31] carried out a study into the performance and disruptiveness of visual, audio, tactile and olfactory notifications and found that modality did not affect error or activity rates, but did provide different response accuracies and timings. In their experiment, all of the notifications required a response.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations